Trauma, historical injustices and affect : the vicissitudes of womanhood in Zimbabwe in Tsitsi Dangarembga’s This Mournable Body (2018) - Medalie, David (University of Pretoria, 2021)
Mini Dissertation (MA (Creative Writing))--University of Pretoria, 2021.